2013
DOI: 10.1002/ajmg.a.36225
|View full text |Cite
|
Sign up to set email alerts
|

17p13.1 microdeletion: Genetic and clinical findings in a new patient with epilepsy and comparison with literature

Abstract: Array comparative genomic hybridization is now a powerful tool to investigate patients with multiple congenital abnormalities and intellectual/motor impairment, and genomic imbalances are identified in a growing number of children with intellectual disability. Deletions in the 17p13.1 region have been reported in patients with dysmorphic features and developmental delay but a consistent phenotype has yet to emerge. Here, we report on the diagnosis of a 17p13.1 microdeletion of 829 kb in an 8-year-old girl pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 16 publications
2
11
0
Order By: Relevance
“…The FXR2 gene is located on chromosome 17. Microdeletions in the 17p13.1 comprise a syndrome that is often associated with dysmorphic features and developmental delay [16,17]. Given that this microdeletion syndrome is accompanied by the loss of multiple genes, it is hard to identify the specific role of FXR2 .…”
Section: Introductionmentioning
confidence: 99%
“…The FXR2 gene is located on chromosome 17. Microdeletions in the 17p13.1 comprise a syndrome that is often associated with dysmorphic features and developmental delay [16,17]. Given that this microdeletion syndrome is accompanied by the loss of multiple genes, it is hard to identify the specific role of FXR2 .…”
Section: Introductionmentioning
confidence: 99%
“…Our patients and the previously reported patients with microduplications of 17p13.1 have overlapping clinical features including neurodevelopmental delays and absolute/relative macrocephaly (Table ). Neurodevelopmental delays and microcephaly have previously been associated with microdeletions of 17p13.1 [Adam et al, ; Krepischi‐Santos et al, ; Schwarzbraun et al, ; Komoike et al, ; Schluth‐Bolard et al, ; Shlien et al, ; Zeesman et al, ; Giordano et al, ]. Microcephaly and macrocephaly have been reported in individuals with reciprocal microdeletions and microduplications, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Microduplications of chromosome 17p13.1 have recently been reported to be associated with neurodevelopmental delays [Belligni et al, ; Coutton et al, ]. Microdeletions associated with neurodevelopmental delays and microcephaly which overlap the same region of 17p13.1 have previously been reported in 16 patients [Adam et al, ; Krepischi‐Santos et al, ; Schwarzbraun et al, ; Komoike et al, ; Schluth‐Bolard et al, ; Shlien et al, ; Zeesman et al, ; Giordano et al, ]. It has been proposed that alteration of a dose‐dependent gene may be responsible for the neurodevelopmental delays in individuals with overlapping microdeletions and microduplications of 17p13.1 [Belligni et al, ; Coutton et al, ].…”
Section: Introductionmentioning
confidence: 98%
“…Beyond repeat expansions in the FMR1 gene, a number of rare pathogenic point mutations have been reported that cause developmental delay and ID reminiscent of FXS [153][154][155][156][157]. Further evidence suggests that mutations in the autosomal homolog FXR2 gene might also contribute to ID [158][159][160]. Whilst variants affecting the related FXR1 gene confer risk to schizophrenia, bipolar disorder, and autism [161][162][163][164][165], the genetic link between FMR1 and psychiatric disorders derives from enrichment of association within the gene targets of FMRP (among which the fragile-X family genes themselves are included).…”
Section: Fmrp and Fmrp Targets In Psychiatric Genomic Studiesmentioning
confidence: 99%